The multidimensional housing deprivation Local dynamics of inequality, policies and challenges for the future - BERGAMASCHI, MAURIZIO (Sociologia del territorio, 2022)
The book, within the framework of the activities of the H2020 MICADO (Migrant Integration Cockpits and Dashboards) project, brings together a set of contributions on contemporary housing, which represents one of the areas, although not the only one, in which migrants experience a condition of major vulnerability compared to the native population and that hinders their full integration in their new living context and full social participation. This contribution, organized in three thematic sessions (Public Housing Policies and Practices; Settlement Spaces and Mechanisms of Ethnic Residential Segregation; Housing and New Technologies), analyzes housing needs both from a theoretical point of view, to prompt insights into the distinctive features of the new housing issue, but also by reporting the findings of empirical research that can provide elements of evaluation and methodological indications on the topic.